Evaluación del crecimiento dasométrico de Gmelina arborea Roxb (MELINA) procedente de Costa Rica y Ecuador, en la comuna el Cóndor del Cantón Valencia Provincia de Los Ríos, II fase. - Alvarez Galarza, Wagner Ricardo (2014)
This research was conducted in the municipality of the Condor, canton Valencia, province of Los Rios, with the aim of evaluating the growth dasometric Gmelina arborea Roxb (Melina) from Costa Rica and Ecuador, the research was conducted in a plantation of Gmelina 4 years old, established as a pure plantation spacing of 3 x 3, the sample was made permanent growth plots and the results compared with the investigation of the first phase of this plantation. In the present investigation the Gmelina Coast Rica presented a DAP of 17.04 cm. Facing the seed source of Ecuador with 13.71 cm. The total height of the origin of Ecuador was 7 m, compared to that of Costa Rica with 15sqm. Also the IMA of Costa Rica was at 0.1071 against Ecuador 0.060725 AB and the origin of Costa Rica with 0.0221 cm2 was higher compared to that of Ecuador with 0.0189 cm2. To determine the quality of the trees was assessed based on their phytosanitary status in three class A, B and C, being the excellent category A, B and C good bad, to get the number of individuals per diameter class ranges were established; for A greater than 15.10; B 12.10 C 15.00 and less than 12.00 cm, this allowed to have a data categories and calculate percentages thinning of category C.